Statement before the Economic and Social Council - Black, Eugene R. (World Bank, Washington, DC, 2019)
Eugene R. Black, President of the International Bank for Reconstruction and Development, reviewed the scope of the Bank’s lending. While the first loans were for reconstruction, the principal business has been development loans for such things as electric power, agricultural machinery, timber production, woodworking industry, railways, and shipping. He spoke of the technical examinations of particular projects and the high lending standards imposed. He mentioned the technical aid which Bank has provided and expects this to widen. The Bank’s essential objective is to raise production levels and living standards through long-term project financing, technical advice, and stimulation to private investment.